The Influence of Work Discipline, Incentives, and Work Motivation on Employee Performance at PT Citra Mandiri Distribusindo - Jessyca Jessyca; Mauli Siagian (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the influence of work discipline, incentives, and work motivation on employee performance at PT Citra Mandiri Distribusindo. The background of this research is based on issues such as low employee discipline, unequal incentive distribution, and lack of motivation, which lead to fluctuating employee performance. The research used a descriptive quantitative method with a survey approach, employing questionnaires distributed to all employees except Directors, General Managers, and HRD, with a total of 109 respondents. The data analysis technique used multiple linear regression to examine the influence of each variable. The results showed that partially and simultaneously, work discipline, incentives, and work motivation significantly influence employee performance. The implication of this research is that the company must enhance employee discipline, clarify the incentive system, and foster motivation through effective communication and recognition to achieve optimal employee performance.